Employee perspectives on the association of work stress and mental health at an institution of higher learning in the Western Cape Province, Southern Africa - Mbambo, Samukelisiwe (Department of Psychology, 2024)
Work stress has been identified as an epidemic within the workplace in South Africa and other parts of the world. Work stress has been shown to negatively affect employees' mental health, leading to the onset or exacerbation of common mental disorders such as chronic depression and anxiety. A strong body of evidence suggests that higher education institutions are high stress environments. Therefore, employees in higher education institutions experience significant work stress, resulting in poor mental health. A number of studies have investigated the link between work stress and mental health. However, there is a paucity of research on how local academic staff experience the impact of work stress on their psychological well-being and mental health. The aim of this study was to investigate employees' experiences of work stress, and the impact thereof on their mental health. A qualitative methodological approach was utilised. Eligible participants were academic staff from a local tertiary institution. Semistructured interviews were utilised in a virtual format, and data was analysed using thematic analysis. The four themes that emerged from the analysis were reported in two categories. The findings revealed the adverse impact of work stress on psychological well-being, and also shed light on how academic staff members cope with work stress and improve their psychological well-being and mental health. Therefore, there is a negative association between work stress and mental health, and academic employees are making use of varying coping mechanisms to curb the impact of stress on their mental health such as attending therapy sessions, engaging support systems, and creating boundaries, for example, planning, organising, and time management, especially during the Covid-19 pandemic. Finally, the findings of this study contribute to the existing body of knowledge on the relationship between work stress and mental health in the workplace from a South African perspective. Keywords: academic staff; mental health; psychological well-being; qualitative research; higher education institutions (HEIs); thematic analysis; work stress; work stressors.